Growing into teen fatherhood: a grounded theory study - C. Uengwongsapat (2018)
© 2017 International Council of Nurses Background: Becoming an adolescent father is a significant and critical life event. Expectant fathers are faced with a concurrent dual developmental crisis: being an adolescent and becoming a father. This transition has a tremendous impact on these adolescents, their families and society. The impact on these individuals and society does not, at this point, seem to be clearly understood. Purpose: To explore the process of Thai adolescents becoming first-time fathers with an unplanned pregnancy during their girlfriend's pregnancy. Methods: A grounded theory approach was used, drawing upon semi-structured interviews with 16 expectant fathers in Chiang Mai, Thailand. Findings: ‘Growing into teen fatherhood’ was the basic social process that emerged as the core category. These fathers used this process for developing themselves to fatherhood. This process was further divided into three phases: enduring the conflict of future role, accepting impending fatherhood and developing a sense of being teen expectant father. Throughout this process, the participants encountered many conflicts and challenges. They employed various strategies to manage the emotional, financial and interpersonal challenges they faced during the transition to fatherhood. Conclusion: This study provides data as well as anecdotal evidence for healthcare professionals to better understand adolescent fathers and their unique challenges during their girlfriend's pregnancy. A better understanding of these rich findings will enable healthcare professionals to assist young men and boys in their struggle to transition to fatherhood. Implications for nursing policy: Our data may guide policymakers in developing support groups, effective mentoring programs and national follow-up services as standard services in hospitals’ care for first-time adolescent fathers in Thailand.